STRUCTURE OF HUMAN SKELETON EXHIBITS THE MYSTERIOUS LOVE OF ALLAH (SWT) TO PROPHET MUHAMMAD (SAW) - Hossain, Mohammad Abul (Ar Raniry : International Journal of Islamic Studies, 2018)
This study presents a scientific explanation of a very important verse (Ayat), 95:4 in the holy QurÃ¢â‚¬â„¢an. The verse is in sura At-Tin, states that: Ã™â€žÃ™Å½Ã™â€šÃ™Å½Ã˜Â¯Ã™â€™ Ã˜Â®Ã™Å½Ã™â€žÃ™Å½Ã™â€šÃ™â€™Ã™â€ Ã™Å½Ã˜Â§ Ã˜Â§Ã™â€žÃ™â€™Ã˜Â¥Ã™ÂÃ™â€ Ã˜Â³Ã™Å½Ã˜Â§Ã™â€ Ã™Å½ Ã™ÂÃ™ÂÃ™Å  Ã˜Â£Ã™Å½Ã˜ÂÃ™â€™Ã˜Â³Ã™Å½Ã™â€ Ã™Â Ã˜ÂªÃ™Å½Ã™â€šÃ™â€™Ã™Ë†Ã™ÂÃ™Å Ã™â€¦Ã™Â - Ã‚Â Ã‚Â : Ã¢â‚¬Å“Verily, We created man in the best statue (mould)Ã¢â‚¬Â. In response to the Ã¢â‚¬Å“best statueÃ¢â‚¬Â, a mysterious observation is proposed by correlating the four oaths of Allah (Sobhan wa tawla: SWT) which imposed before starting this verse, with the help of physical structure of oath materials, knowledge of medical science and other verses in the holy QurÃ¢â‚¬â„¢an. That is Ã¢â‚¬â€œ the statue of human body (Adam) represents the combine structure of Arabic wordsÃ‚Â Muhammad (Peace be upon him: PBUH) and Allah (SWT), which made his (Adam) superiority to all others. Thus human became the topmost creature in the whole universe, and his body structure is created in the best statue, mentioned in the verse of the holy QurÃ¢â‚¬â„¢an. Actually, the creation of such structure of human body is the outlooks of the infinite love of Allah (SWT) to His prophet Muhammad (SAW). Regarding this, supporting verses in the holy QurÃ¢â‚¬â„¢an are discussed. Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â